Examining the Role of Work Motivation and Teacher Competence on Career Development: the Mediating Role of Job Satisfaction among Teachers in the South Nias Regency - Tafonao, Lince Kristina; Darmayanti, Nefi; Lubis, Rahmi (Universitas Ahmad Dahlan, 2024)
This study aimed to investigate teacher career development, workplace motivation, teacher competencies, and job satisfaction. Utilizing a quantitative explanatory approach, the study included 306 teachers selected through a cluster random sampling technique. Structural Equation Modeling (SEM) analysis was employed with the assistance of Smart-PLS software. The findings indicate a significant impact of work motivation on career development among teachers in the South Nias Regency area. Furthermore, teacher competencies were found to influence career development in the same region. Additionally, work motivation exerted a noteworthy effect on job satisfaction among teachers, while competencies also played a role in influencing job satisfaction. Moreover, job satisfaction was identified as a contributing factor to career development. Finally, the study revealed that work motivation and competencies affect career development through the mediation of job satisfaction among teachers in the South Nias Regency area.